Mesenteric cystic lymphangioma a mimicking the pelvic tumor: Case report - Do?an Artaş, Zeynep; Çelik, Hüsnü; Gürateş, Bilgin; Aygen, Erhan; Artaş, Hakan; Yavuz, Adem; Özercan, M. Reşat (My University, 2010)
Lymphangioma is an uncommon benign tumor of the lymphatic vessels. Most of the lymphangiomas are found in head, neck and axilla. It is rare in adults and abdominal location is infrequent. Its treatment is resection of the cystic mass entirely. The prognosis is excellent with total resection, but high incidence of recurrence has been reported in case of incomplete resections. Herein, we present a 32-year-old woman who submitted with abdominal distention. She had a history of previous ovarian cyst surgery. Abdominal ultrasound and computed tomography showed multiple cystic masses in the pelvis. The case was operated and, histopathological diagnosis was reported as cystic lymphangioma during follow-up, recurrence was detected in pelvis in the second year of the postoperative period. Copyright © 2010 by Türkiye Klinikleri.
Pelvik tümörü taklit eden mezenterik kistik lenfanjiyom
Keywords: Cystic; Lymphangioma; Mesenteric cyst; Pelvic neoplasms; Surgery